(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The current state of researches of the floodplain forest and shrub vegetation on the territory of Ukraine is highlighted. The overview of the most important floristic and geobotanical works was made. The history of research in the region is divided into different types and presented in chronological order. The characteristics of research results of Ukrainian scientists in the floristic, geobotanical, ecological and phytosozological directions are given, and current research tasks for the future are defined. On the basis of the literature sources, which provide information about the flora and vegetation of the floodplain forests, it is possible to see the history of the development of their research from the middle of the 19th century to the present day. At the same time, it is noted that in the 19th and early 20th centuries, geobotanical researches had a general character. Only in the 30s of the 20th century, more attention was paid to different types of vegetation. Special attention is focused on the geobotanical works, which are the basis for the study of all types of vegetation, and floodplains, in particular. It was found that the number of publications that contain information about the floodplain forests of Ukraine is quite large, but there are few publications that are devoted exclusively to this type of vegetation. They appeared, with some exceptions, only in the end of the 20th century. Generally scientists were not focused on the floodplain forests. This fact was repeatedly noted by various scientists. In the future, it is necessary to carry out a syntaxonomic revision of the classes Alnetea glutinosae and Salicetea purpureae, since the number of associations described by geobotanists from the territory of Ukraine is disproportionately large. It is important to study the flora of floodplain forests, because there is no general list of species that occur in this vegetation type. There is no understanding of which alien species occur in this habitat type and to which extend they affected by alien plant invasions. A number of ecological issues remain unresolved. It was found that the floodplains of large rivers of Ukraine, such as Dnipro and Siverskyi Donets, are studied appropriately well. The floodplains of small rivers, especially in the Carpathians and in the western regions of Ukraine, have actually been studied very little, so there are still many objectives in the study of floodplain forests for the future.